World strongest 200m sprinters` competitive performance analysis - Mirzoev, O. M. (Theory and Practice of Physical Culture, 2018)
The study offers the 2017 world strongest 200m sprinters` competitive performance analysis with a special emphasis on a few key aspects of the performance. The aspects subject to a special analysis were the following: 0-100m and 100-200m interval times; interval time differences on the distance; time difference between the individual best 100m time and the 100-200m interval time; deceleration rate in the second half-distance versus the first one; interim result of each athlete in every interval on the 200m distance etc. Subject to the analysis was the competitive performance of the finalists in the 2017 IAAF World Championship in London versus their progress data for the period of 2000-2017 - that generally show a growing trend followed with some sag. The study found, among other things, that the competitive success largely depends on the second 100-200m interval time.